Mercury and Organomercurial Resistances Determined by Plasmids in Staphylococcus aureus - Weiss, Alison A. (1977)
Penicillinase plasmids of Staphylococcus aureus often contain genes conferring resistance to inorganic mercury (Hg(2+)) and the organomercurial phenylmercury acetate. The mechanism of resistance was found to be the enzymatic hydrolysis of the organomercurial phenylmercury to benzene plus inorganic ionic mercury, which was then enzymatically reduced to metallic mercury (Hg(0)). The Hg(0) was rapidly volatilized from the medium into the atmosphere. After the mercurial was degraded and the mercury was volatilized, the resistant cells were able to grow. These plasmids also conferred the ability to volatilize mercury from thimerosal, although the plasmid-bearing strains were equally as thimerosal sensitive as the S. aureus without plasmids. None of the plasmids conferred the ability to volatilize mercury from several other organomercurials, however: methylmercury, ethylmercury, p-hydroxymercuribenzoate, merbromin, and fluorescein mercuric acetate. (Organomercurial resistance-conferring plasmids of Escherichia coli and Pseudomonas aeruginosa that we have been studying confer the ability to degrade two or three of these organomercurials.) Although mercury was not volatilized from p-hydroxymercuribenzoate or fluorescein mercuric acetate, the plasmid-bearing strains were resistant to these organomercurials. The ability to volatilize mercury from Hg(2+) and phenylmercury was inducible. The range of inducers included Hg(2+), phenylmercury, and several organomercurials that were not substrates for the degradation system. Mercury-sensitive mutants have been isolated from the parental plasmids pI258 and pII147. Thirty-one such mercury-sensitive strains fall into three classes: (i) mercury-sensitive strains totally devoid of the phenylmercury hydrolase and Hg(2+) reductase activities; (ii) mutants with normal hydrolase levels and no detectable reductase; and (iii) mutants with essentially normal hydrolase levels and low and variable (5 to 25%) levels of reductase activities. The mercury-sensitive strains were also sensitive to phenylmercury, including those with the potential for hydrolase activity.